Chemical and physical defense traits in two sexual forms of Opuntia robusta in Central Eastern Mexico. - Mariusz Krzysztof Janczur; Héctor Javier León Solano; Lupita Tzenyatze Solache Rámos; Citlalli Hypatia Mendoza Reyes; María del Carmen Oro Cerro; María Dolores Mariezcurrena Berasain; Irma Victoria Rivas Manzano; Javier Manjarrez; José Luis Villareal Benitez; Marcin Czarnoleski (PLoS ONE)
Sexually dimorphic plants provide an excellent opportunity for examining the differences in the extent of their defense against herbivores because they exhibit sex-related differences in reproductive investment. Such differences enable comparison of the sex with high reproduction expenses with the sex that expends less. The more costly sex is usually also better defended against herbivores. Generally, females are considered more valuable than hermaphrodites in terms of fitness; however, hermaphrodites are more valuable if they can produce seed by autonomous selfing, provided that the inbreeding depression is low and pollen is limited. We studied a gynodioecious population of Opuntia robusta from Central-Eastern Mexico, which has been reported to be trioecious, dioecious, or hermaphrodite, and addressed the following questions: 1) Is the hermaphrodite's reproductive output higher than the female's, and are hermaphrodites thus better defended? 2) Are plant tissues differentially defended? 3) Do trade-offs exist among different physical defense traits? and 4) among physical and chemical defense traits? We found that 1) hermaphrodites had a higher seed output and more spines per areola than females and that their spines contained less moisture. Non-reproductive hermaphrodite cladodes contained more total phenolic compounds (TPCs) than female ones. In addition, 2) hermaphrodite reproductive cladodes bore more spines than female cladodes, and 3) and 4) we found a negative relationship between spine number per areola and areola number per cladode and a positive relationship between spine number per areola per plant and TPC concentration per plant. Non-reproductive hermaphrodite cladodes contained a higher concentration of TPCs than female cladodes, and parental cladodes contained fewer TPCs than both reproductive and empty cladodes.